Dietary Diversity among Children Aged 12-23 Months in Urban Area - Eka Mishbahatul Marah Has; Nursalam .; Yuni Sufyanti Arief (Journal of Global Pharma Technology, 2020)
This study aimed to describe the dietary diversity among 12-23 months old children living in an urban area. A cross-sectional survey which involved 146 mothers who had children aged 12-23 months, living in Surabaya City, East Java, was conducted. Mother's, child's, household's characteristics, and child's dietary diversity were collected by using a questionnaire. Then, the frequency distribution and percentage analysis were performed. The result showed that most children (96.6%) met the minimum dietary diversity as recommended by WHO. The food groups which mainly consumed were vitamin A-rich fruits and vegetables (100%) and grains, roots, and tubers (96.6%). In reverse, the food groups which less consumed were other fruits and vegetables, and legumes and nuts. Integrated health promotion is needed to ensure low socioeconomic status household who lived in the urban area met the appropriate infant and young child feeding practice. Keywords: Dietary diversity; Children aged 12-23 months; Urban area.